Pengaruh Sosialisasi Perpajakan, Kualitas Pelayanan Fiskus Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan Perdesaan Dan Perkotaan (PBB-P2) (Studi Pada Kabupaten Buleleng): (Studi pada Kabupaten Buleleng) - Gede Wiranata, Pande; Ari Surya Darmawan, Nyoman (Universitas Pendidikan Ganesha, 2025)
This study aims to examine the influence of tax socialization, the quality of tax officer services, and taxpayer awareness on the compliance of Rural and Urban Land and Building Tax (PBB-P2) taxpayers in Buleleng Regency. The research method used is causal associative with a quantitative approach. The sample size in this study consists of 100 respondents. The sampling technique employed is purposive sampling. Data were collected through the distribution of questionnaires. Data analysis was conducted using multiple linear regression analysis with the assistance of SPSS version 25. The results of this study reveal that tax socialization has a significant positive effect on taxpayer compliance, the quality of tax officer services has a significant positive effect on taxpayer compliance, and taxpayer awareness also has a significant positive effect on taxpayer compliance